2020
DOI: 10.1186/s12870-020-02387-3
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression and genetic control to cold tolerance during maize seed germination

Abstract: Background: The study of cold tolerance in maize seeds and seedlings through physiological quality assessments, as well as the genetic control associated with this trait, allows an early characterization of genotypes. Here we studied the genetic control for cold tolerance during the germination process in maize seeds and genes influenced by this stress. Results: Six maize lines were used, three classified as tolerant and three as susceptible to low germination temperature. A field was developed to produce the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Quantitative genetic analyses of cold tolerance have shown that genotype, additive effects, growth stage, heterosis, and reciprocal and environmental factors are all involved in the expression of cold tolerance in maize [46]. Six maize lines were used to evaluate the expression of CAT, APX, SOD, and other genes; the results showed that there was heterosis for germination under cold stress, and non-additive genes were more important [47]. The studies cited above show that the genetics mechanisms of low-temperature tolerance in maize are very complicated.…”
Section: Discussionmentioning
confidence: 99%
“…Quantitative genetic analyses of cold tolerance have shown that genotype, additive effects, growth stage, heterosis, and reciprocal and environmental factors are all involved in the expression of cold tolerance in maize [46]. Six maize lines were used to evaluate the expression of CAT, APX, SOD, and other genes; the results showed that there was heterosis for germination under cold stress, and non-additive genes were more important [47]. The studies cited above show that the genetics mechanisms of low-temperature tolerance in maize are very complicated.…”
Section: Discussionmentioning
confidence: 99%
“…A volume of 60 µL of the sample supernatant was applied to the gel, and the electrophoretic run was performed at 150 V for 5 hours. After the run, the gels were used to detect the activities of SOD and CAT enzymes, following the methods described by Silva Neta et al (2020).…”
Section: Analysis Of Superoxide Dismutase and Catalasementioning
confidence: 99%
“…The enzymatic activity of peroxidase (POX), superoxide dismutase (SOD), and catalase (CAT) was determined by electrophoresis (Silva Neta et al, 2020). 1 g of fresh matter was extracted into 0.2 M Tris-HCl buffer pH 8.0 + 0.1% beta-mercaptoethanol for SOD and CAT, and for the POX enzyme, potassium phosphate buffer was used at a ratio of 300 µL per 100 mg of fresh weight.…”
Section: Enzymatic Activitymentioning
confidence: 99%